Should All Men with Type 2 Diabetes Be Routinely Prescribed a Phosphodiesterase Type 5 Inhibitor? - Hackett, Geoffrey (World J Mens Health, 2020)
Important health problems in men such as type 2 diabetes (T2DM), insulin resistance, erectile dysfunction, benign prostatic hyperplasia and depression have been shown to have to share common pathological processes, such as endothelial dysfunction and inflammation. This paper discusses the role of phosphodiesterase type 5 (PDE5) inhibitors, through beneficial effects on endothelial function and mediators of chronic inflammation and the possibility to treat or preventing these common conditions. We explore possible barriers to this approach, namely the lack of multiple product licences to treat each of these conditions and how these can be overcome by involving the patient in personalised decisions. We also discuss how opportunities are lost by patients with multiple medical conditions being referred to specialists, primarily interested in one specific problem, with little motivation to treat or prevent conditions outside their remit. We explore how these problems might be related to time and financial restraints or simply a lack of awareness of evidence published in journals related to other specialities. As specialists, we often pride ourselves on providing “personalised” or “patient centred” care, but we can only truly be doing so if we assess the specific needs of the patient across a range of conditions. As part of personalised care in T2DM, we routinely prescribe statins, angiotensin converting enzyme inhibitors and metformin, often with poor compliance. In this paper we explore whether the licensed daily PDE5 inhibitor tadalafil should be added routinely to this list as it will potentially improve and prevent bothersome symptoms and improve compliance with other medications.